Bacillus cereus in food safety: a bibliometric analysis - Abdul, Muhammad-Ehtesham; Pavoni, Enrico (Frontiers in Microbiology, 2025)
Bacillus cereus, a spore-forming pathogen, poses significant food safety risks due to its prevalence in diverse food matrices and ability to produce emetic and diarrheal toxins. This study presents the first bibliometric analysis of global research on B. cereus in food safety, examining 898 Scopus-indexed articles (2000–2024). Data were extracted using the search query “Bacillus cereus” OR “B. cereus” AND “Food Safety” in titles/abstracts, followed by quantitative and visual analyses via VOSviewer and the bibliometrix R-package. Metrics included annual growth rates, citation trends, country/institution contributions, and keyword co-occurrence. Collaborative networks and author productivity were mapped using co-authorship analysis. Results revealed an 8.29% annual publication growth, with China (38.86%), South Korea (22.05%), and the United States (18.26%) as leading contributors. Citation analysis highlighted seminal works on pathogenicity (e.g., enterotoxins, antimicrobial resistance), while keyword co-occurrence identified emerging themes such as virulence genes, cereulide, and sustainable mitigation strategies (e.g., probiotics, bacteriocins). Critical gaps persist in understanding B. cereus behavior in novel food matrices (e.g., plant-based alternatives) and the efficacy of emerging preservation technologies. This analysis underscores the need for interdisciplinary approaches integrating genomics, food science, and public health to address risks in global supply chains. The findings provide a roadmap for future research, advocating for advanced surveillance, innovative interventions, and policy refinement to combat this resilient pathogen.